Pengembangan Bahan Ajar IPAS yang Berbantuan Augmented Reality di Kelas V Sekolah Dasar Negeri Podorejo 02 - Firstyansa Heriyanto; Eka Titi Andaryani (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to determine how Augmented Reality Teaching Materials can improve students' understanding and skills, given that students initially had difficulty understanding the material because the teaching method used was still the old method, commonly known as the lecture method. Here, the researcher presents a new learning concept, namely using a learning method in which students are actively involved in learning. The researcher uses the ADDIE research method, in which this research begins with At this stage, initial observations were conducted at SDN Podorejo 02, with m pages and classrooms, and a direct meeting with the principal. Next, communication with the fifth-grade homeroom teacher about IPAS subjects. The researcher analyzed how fifth-grade, After conducting an analysis and identifying the problems from the school's analysis, the researcher attempted to design and create a highly interactive learning medium that follows technological developments to replace the old learning method, which only used thick printed books and lectures, Next, for this stage, the development product is ready to be created according to the plan made by the researcher; learning media is prepared, and media is created. Media experts and material experts in their fields are also referred to as teachers, whose job is to guide and check whether the material from the media complies with existing regulations to ensure its validity. After conducting a series of tests through media experts and after going through the revision stage, the next step is  to implement the media to students to see whether or not this learning media can improve student learning outcomes. After implementing the media created at Podorejo 02 Public Elementary School, the next step is to evaluate the results of the implementation which involves conducting a formative and summative evaluation to measure whether this media can improve student learning outcomes in Grade V IPAS lessons. And then this conclusion this Based on the results of the research and discussion of teaching materials assisted by Augmented Reality in IPAS lessons at Podorejo 02 Public Elementary School, the following conclusions can be drawn: Development of teaching materials assisted by Augmented Reality in IPAS lessons at Podorejo 02 Public Elementary School using the ADDIE method on the Assemblr Edu website, which shows 3D and AR technology that functions as a teaching medium that can display the shape of objects or images in 3D. Based on the responses from the students, a score of 69% was obtained, indicating an increase from the initial stage where the students did not understand the material to the stage where they became familiar with it. Therefore, this medium is categorized as suitable for use.